Comparison of Pet Owners and Non-Pet Owners in Terms of Depression, Anxiety and Quality of Life - Yalçın Kahya; Ali Erdoğan (Genel Tıp Dergisi)
Objective: In this study, it was aimed to compare pet owners and non-pet owners in terms of depression, anxiety and quality of life. Methods: A total of 397 healthy volunteers over the age of 18, 192 pet owners, and 205 non-pet owners were included in our study. Sociodemographic data form, World Health Organization Quality of Life Scale-Short Form (SF-36), and Hospital Anxiety and Depression Scale (HADS) were administered to all participants. Results: Of all participants, 60.2% (n=239) were female and 39.8% (n=158) were male. The mean age of pet owners (36.74±9.56) was similar to non-pet owners (35.52±9.16) (p=0.194). The mean depression scores of pet owners (4.39±3.37) were significantly lower than non-pet owners (6.02±3.72) (p